Python online exam system - Chan, Shaw Wei Zhe (2019)
With the advancement in information technology, programming skills have rapidly garnered interests among students and this led to an increasing number of students enrolled in programming courses. Due to the complexity of programming skills, it has been reported that both students and instructors are having difficulties in learning and teaching respectively. This project aims to develop an online web application that possesses better capabilities by allowing both students to practice their programming skill on specific programming topics and for instructors to monitor the students’ work. In this project, a web-based platform for the online exam system, named Quizsys+, is proposed. It supports the creation of various types of questions, such as multiple-choice and programming questions. For programming, the system will use the test cases provided to grade students’ codes. In this report, it will cover practice components of the system and the production of the system. For practice mode, students can attempt questions of any topic with unlimited tries. Upon submission, the instructor will be able to view students’ performance using system graphical representation to gain insight on the class’ capability. For the production of the system, it will be deployed on IIS web server for both front-end and back-end of the system. This project has completely deployed into production and is currently used by students studying introductory to programming courses. Possible future works for this project may include the extension of other programming language and challenge mode.